Movimento STEM no ambiente escolar: perspectivas para o ensino médio do Rio Grande do Sul - Brum, Ariane Prates (2023)
This dissertation presents an analysis of the STEM (Science, Technology, Engineering, and Mathematics) movement in the school environment, with a focus on the perspectives for high school education in the state of Rio Grande do Sul (RS), Brazil. To achieve this, a State of the Art was conducted, containing data on publications related to the STEM/STEAM term published in the last 20 years in Brazil, aiming to comprehend the current state and scope of this educational approach in the Brazilian context. The literature review revealed a limited number of published works on the topic in the country, indicating a gap in knowledge or dissemination of practices and research in this area. However, there has been an increase in interest and importance attributed to the topic over the years. Based on this panorama, interviews were conducted with teachers who participated in a STEM Journey organized by Grupo de Estudos do Movimento STEM, affiliated with the Instituto Federal Farroupilha and the Universidade Federal de Santa Maria. The purpose of these interviews was to collect information on the challenges and potentialities of STEM education for high school in RS. The interviews provided a deeper understanding of the practices, perspectives, and personal experiences of the teachers involved in implementing the STEM approach. The collected data is being analyzed using Content Analysis (BARDIN). The collected data requires a final analysis to obtain accurate and evidence-based conclusions, contributing to the advancement of research in the field and guiding future studies.